2013
DOI: 10.1179/1973947813y.0000000081
|View full text |Cite
|
Sign up to set email alerts
|

Maternal carriage of extended-spectrum beta-lactamase-producingEscherichia coliisolates in Argentina

Abstract: The aim of this study was to determine the prevalence of vaginal Escherichia coli colonization and perianal carriage of Enterobacteriaceae resistant to third generation cephalosporins in pregnant women. Vaginal and perianal samples from 259 pregnant women were studied. Vaginal swabs were inoculated onto MacConkey agar plates and perianal swabs were inoculated onto CHROMagar extended-spectrum beta-lactamase (ESBL) plates. The minimal inhibitory concentration of the isolates was determined using the Epsilometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 11 publications
8
27
1
1
Order By: Relevance
“…Prevalence of antibiotic resistance in the E. coli strains isolated from pregnant women of Tanzania against ampicillin, sulfamethazoletrimethoprim, tetracycline, nitrofurantoin, ceftriaxone, gentamycin, ciprofloxacin and imipenem were 52.9, 64.7, 58.8, 5.9, 29.4, 5.9, 11.8 and 0 %, respectively [25]. Similar results have been reported from Nigeria [25], Iraq [27] and Argentina [28].…”
Section: Discussionsupporting
confidence: 79%
“…Prevalence of antibiotic resistance in the E. coli strains isolated from pregnant women of Tanzania against ampicillin, sulfamethazoletrimethoprim, tetracycline, nitrofurantoin, ceftriaxone, gentamycin, ciprofloxacin and imipenem were 52.9, 64.7, 58.8, 5.9, 29.4, 5.9, 11.8 and 0 %, respectively [25]. Similar results have been reported from Nigeria [25], Iraq [27] and Argentina [28].…”
Section: Discussionsupporting
confidence: 79%
“…[20][21][22][23] Reported carriage rates of ESBL-E in pregnant women range from 7.3 to 15.4%, and are likely to reflect carriage rates in the general healthy population in different regions. 6,[24][25][26] African or Asian origin was a risk factor for being colonized by ESBL-E, possibly due to higher carriage rates in these geographical areas. This is in concordance with a UK study analyzing stool samples from out-patients, where they found a statistically significant difference between carriage in the European (8.1%) and the Middle East/South Asian group (22.8%).…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of E. coli vaginal colonisation in pregnant women ranges from 7% to 20% . One study from Argentina reported peri‐anal colonisation with ESBL‐producing E. coli in 5.4% of pregnant women . As part of an Olympics surveillance project (in collaboration with Public Health England) we have isolated ESBL‐producing Enterobacteriaceae from 20% of women of childbearing age (15–45 years) in north‐east London who submitted stool samples for laboratory examination .…”
Section: Introductionmentioning
confidence: 99%